Effects of antituberculosis treatment on pregnancy outcomes in infertile women with genital tuberculosis: a systematic review - Kevin Flores-Lovon; David R. Soriano‐Moreno; Sebastian A. Medina-Ramírez; Daniel Fernandez‐Guzman; Brenda Caira‐Chuquineyra; Jared Fernandez-Morales; Kimberly G. Tuco; John Turpo-Prieto; Jorge Alave; Sergio Goicochea-Lugo (My University, 2023)
OBJECTIVES: To evaluate the efficacy of antituberculosis therapy on pregnancy outcomes in infertile women with genital tuberculosis. DESIGN: Systematic review. DATA SOURCES: We searched in PubMed/MEDLINE, CENTRAL and EMBASE up to 15 January 2023. Additionally, we manually search the reference lists of included studies. ELIGIBILITY CRITERIA: We included randomised controlled trials (RCT), non-RCTs (non-RCT) and cohort studies that evaluated the effects of antituberculosis treatment on pregnancy outcomes in infertile women with genital tuberculosis compared with not receiving antituberculosis treatment or receiving the treatment for a shorter period. DATA EXTRACTION AND SYNTHESIS: Two independent reviewers extracted data. We used Cochrane Risk of Bias 1.0 and Risk Of Bias In Non-randomised Studies tools for risk of bias assessment and meta-analysis was not performed. We used Grading of Recommendations, Assessment, Development and Evaluations approach to assess the certainty of the evidence. RESULTS: Two RCTs and one non-RCT were included. The antituberculosis regimens were based on isoniazid, rifampicin, pyrazinamide and ethambutol for 6-12 months. In women without structural damage, very low certainty of evidence from one RCT showed that the antituberculosis treatment may have little to no effect on pregnancy, full-term pregnancy, abortion or intrauterine death and ectopic pregnancy, but the evidence is very uncertain. In women with structural damage, very low certainty of evidence from one non-RCT showed that the antituberculosis treatment may reduce the pregnancy rate (297 fewer per 1000, 95% CI -416 to -101), but the evidence is very uncertain. In addition, very low certainty of evidence from one RCT compared a 9-month vs 6-month antituberculosis treatment regimen showed similar effects between the schemes, but the evidence is very uncertain. Two RCTs reported that no adverse events of antituberculosis treatment were noted or were similar in both groups. CONCLUSION: The effect of antituberculosis treatment on pregnancy outcomes in infertile women with genital tuberculosis is very uncertain. PROSPERO REGISTRATION NUMBER: CRD42022273145.
Keywords: Medicine; Randomized controlled trial; Pregnancy; Ethambutol; Tuberculosis; Obstetrics; Pyrazinamide; Gynecology; Rifampicin; Internal medicine; Genetics; Pathology; Biology; Medicine; Randomized controlled trial; Pregnancy; Ethambutol; Tuberculosis; Obstetrics; Pyrazinamide; Gynecology; Rifampicin; Internal medicine; Antitubercular Agents therapeutic use; Antitubercular Agents therapeutic use; Antitubercular Agents therapeutic use; Female; Female; Female; Genitalia; Genitalia; Genitalia; Humans; Humans; Humans; Infertility, Female drug therapy; Infertility, Female drug therapy; Infertility, Female drug therapy; Infertility, Female etiology; Infertility, Female etiology; Infertility, Female etiology; Pregnancy; Pregnancy; Pregnancy; Pregnancy Outcome; Pregnancy Outcome; Pregnancy Outcome; Tuberculosis; Tuberculosis; Tuberculosis; Stillbirth; Stillbirth; Stillbirth; Health Sciences Medicine Surgery Diagnosis and treatment of tuberculosis; Health Sciences Medicine Surgery Infectious Diseases and Tuberculosis; Health Sciences Medicine Public Health, Environmental and Occupational Health Pregnancy and Medication Impact